Erratum: Continuum-wise expansiveness for generic diffeomorphisms (2018 Nonlinearity31 2982). (12th April 2019) - Lee, Manseob
Abstract : The opportunity has been taken to update the wording of the original abstract to improve its clarity. Abstract Let M be a closed smooth manifold and let be a diffeomorphism. For a C 1 generic diffeomorphism f , if f is continuum-wise expansive then it is Axiom A without cycles. Let and let be a diffeomorphism. There is a C 1 neighborhood of and a residual set such that for any, g is not continuum-wise expansive, where is the set of all robustly transitive diffeomorphisms on